Rapidly growing cardiac mass: a rare case of left atrial intramural hematoma complicating coronary artery stenting. Issue 10 (13th October 2016) - Varshney, Ravi; Chamberlain, Matthew; Rayner‐Hartley, Erin; Kelliher, Edel; Lee, Arthur; Cook, Richard; Fung, Anthony; Gin, Kenneth; Nair, Parvathy; Tsang, Teresa S. M.
Abstract : Formation of an intramural left atrial hematoma (ILAH) is a rare complication of coronary artery stenting. Rapid diagnosis with noninvasive multimodality imaging can potentially be lifesaving. We report a case of ILAH that resulted in left ventricular inflow obstruction and pericardial tamponade in a 55‐year‐old male who presented with hemodynamic instability and worsening dyspnea three weeks after seemingly uncomplicated left circumflex artery stenting. We demonstrate features on transthoracic echocardiography with contrast and cardiac computed tomography that were used for diagnosis and management.